Factors influencing the annual wool growth of Corriedale sheep in Rio Grande do Sul, Brazil - Villarroel, Arturo Bernardo Selaive; Oliveira, Nelson Roberto Manzoni de; Silva, João Gilberto Corrêa da (Pesquisa Agropecuaria Brasileira, 1991)
The effects of season, nutrition level, sex and ewe reproductive status on wool growth were estimated in Corriedale sheep in the state of Rio Grande do Sul. Wool growth, measured by the dye-banding, varied significantly among seasons of the year and between types of pasture (native vs improved). There were no significant differences between ewes and wethers, and no effects of reproductive status upon wool growth. The highest rates of wool growth for sheep grazing on native and improved pasture were respectively recorded in Summer and Spring. It was concluded that photoperiod and nutrition level, mainly concerned with pasture growth, were the major factors affecting the wool growth of sheep in the state of Rio Grande do Sul.